Education with a purpose - Nangia, Ashwini K. (Current Science, 2018)

Co amorphous valsartan nifedipine system: Preparation, characterization, in vitro and in vivo evaluation - Lodagekar, Anurag; Chavan, Rahul B.; Mannava, M. K. Chaitanya; Yadav, Balvant; Chella, Naveen; Nangia, Ashwini K.; Shastri, Nalini R. (European Journal of Pharmaceutical Sciences, 2019)
Co amorphous systems are supersaturated drug delivery systems which offer a basic platform for delivery of multicomponent adducts (combination of more than one active pharmaceutical ingredient (API)) and/or as a fixed dose combination therapy, in addition to their potential to improve the apparent solubility, dissolution rate and ultimately bioavailability of poorly water soluble APIs. In the present work, a new drug-drug co amorphous system namely valsartan-nifedipine was prepared by quench cooling technique. Prepared co amorphous system was characterized for its solid state behavior with the help of Fourier Transform Infrared spectroscopy (FTIR), Differential Scanning Calorimetry (DSC) and Powder X Ray Diffractometry (PXRD). The optimized co amorphous system was stable for 1 month when exposed to accelerated stability condition (40 +/- 2 degrees C and 75 +/- 5% RH). The improved stability of amorphous nifedipine in co amorphous system was attributed to improved miscibility and intra and intermolecular non-covalent interactions mainly due to presence of hydrogen bonding between valsartan and nifedipine which was studied by FTIR analysis. Co amorphous systems were evaluated by mainly in vitro dissolution and in vivo benefit. In vitro dissolution study showed nearly 5.66 folds and 1.61 folds improvement which was translated to 3.63 and 2.19 times enhancement in vivo C-max for nifedipine and valsartan respectively.

Crystal engineering: an outlook for the future - Nangia, Ashwini K.; Desiraju, Gautam R. (Angewandte Chemie-International Edition, 2019)
Crystal Engineering has traditionally dealt with molecular crystals. It is the understanding of intermolecular interactions in the context of crystal packing and in the utilization of such understanding in the design of new solids with desired physical and chemical properties. We outline here five areas which come under the umbrella of Crystal Engineering and where we feel that a proper planning of research efforts could lead to higher dividends for science together with greater returns for humankind. We touch on themes and domains where science funding and translation efforts could be directed in the current climate of a society that increasingly expects applications and utility products from science and technology. The five topics are: 1)pharmaceutical solids; 2)industrial solid state reactions; 3)mechanical properties with practical applications; 4)MOFs and COFs framework solids; 5)new materials for solar energy harvesting and advanced polymers.
Keywords: crystal engineering; metal-organic frameworks; pharmaceutical solids; solar energy; solid-state reactions

Hepatoprotective cocrystals of isoniazid: synthesis, solid state characterization, and hepatotoxicity studies - Yadav, Balvant; Gunnam, Anilkumar; Thipparaboina, Rajesh; Nangia, Ashwini K.; Shastri, Nalini R. (Crystal Growth & Design, 2019)
Isoniazid (INH) is one of the first line drugs used in combination with pyrazinamide and rifampicin for the management of tuberculosis. Idiosyncratic hepatotoxicity is one of the most common side effects of antitubercular therapy worldwide. The current study explores solid phase modification of INH by cocrystallization with various hepatoprotective coformers, namely chrysin, hesperetin, silibinin, syringic acid (SYRA), and quercetin (QUE) to address hepatotoxicity concerns. Cocrystals were obtained with SYRA and QUE. Supramolecular synthons based on pyridine-carboxyl and pyridine-hydroxyl synthon enabled the formation of cocrystals. INHSYRA and INHQUE cocrystals were characterized by FT-IR, DSC, and PXRD. Single crystal X-ray analysis of INHSYRA revealed that it crystallized in triclinic system with the P (1) over bar space group. Intrinsic dissolution rate studies (IDR) showed slow drug release from both the cocrystals. Hepatoprotective effects of INHSYRA and INHQUE cocrystals were evaluated by a single toxic dose study and a subchronic study for 28 days. Results from the subchronic study indicated significant increase in ALT, AST, and ALP enzyme levels in the INH-treated group whereas the enzyme levels in INHSYRA and INHQUE cocrystal treated group were comparable to that of the untreated group. This study demonstrates the in vivo hepatoprotective effects of coformers SYRA and QUE provide promising evidence for utility of nutraceutical based coformers, to tackle hepatotoxicity associated with various drugs.

High-solubility salts of the multiple sclerosis drug teriflunomide - Gunnam, Anilkumar; Nangia, Ashwini K. (Crystal Growth & Design, 2019)
Teriflunomide (TFM) is an immunomodulatory prodrug of leflunomide which is used for the treatment of multiple sclerosis (MS). It is a Biopharmaceutics Classification System Class (BCS) II drug with low solubility and high permeability. The X-ray crystal structure of TFM is stabilized by O-H center dot center dot center dot O, C-H center dot center dot center dot O, C-H center dot center dot center dot N, and N-H center dot center dot center dot N interactions. In order to study the solubility and dissolution changes of this drug, five multicomponent crystal forms were prepared with amine and amide generally regarded as safe (GRAS) coformers to improve the physicochemical properties such as solubility, dissolution, diffusion, and phase stability. Equimolar TFM-coformer 1:1 salts were crystallized, except for cytosine which afforded a salt cocrystal toluene solvate TFM-CYT-TOL in a 1:2:1 ratio. The multicomponent forms were crystallized by slow solvent evaporation and characterized by single crystal X-ray diffraction. TFM and coformer are bonded by N+-H center dot center dot center dot O-, N-H center dot center dot center dot O, O-H center dot center dot center dot O, C-H center dot center dot center dot O, C-H center dot center dot center dot N, N-H center dot center dot center dot N, and C-H center dot center dot center dot F interactions. The bulk phase purity of the salts was characterized by powder X-ray diffraction and infrared and thermal techniques. Solubility, dissolution, and diffusion experiments in pH 7.0 buffer exhibited a significant improvement compared to the reference drug. The morphology and particle size of salts by field emission scanning electron microscopy were related to dissolution behavior. The highest solubility, dissolution, and diffusion profile were observed for TFM-MEA and TFM-TEA salts (monoethanol amine and triethanol amine).

Generation and evaluation of pharmacologically relevant drug-drug cocrystal for gout therapy - Modani, Sheela; Gunnam, Anilkumar; Yadav, Balvant; Nangia, Ashwini K.; Shastri, Nalini R. (Crystal Growth & Design, 2020)
The present study reports a novel drug-drug cocrystal of febuxostat and piroxicam for the treatment of gout. Single crystal X-ray diffraction revealed a monoclinic system with P2(1)/c space group. The prepared cocrystal enhanced the solubility of febuxostat and piroxicam and improved the dissolution rate of piroxicam in pH 6.8 as compared to the pure drug. Further, the compressibility assessment of cocrystal by Aulton and Wells method confirmed its plastic behavior and suitability for direct compression.

Improving the dissolution rate of the anticancer drug dabrafenib - Rai, Sunil K.; Gunnam, Anilkumar; Mannava, M. K. Chaitanya; Nangia, Ashwini K. (Crystal Growth & Design, 2020)
Dabrafenib (DBF) is an anticancer drug with selective B-Raf (BRAF) inhibition activity. In 2013, DBF was approved by the U.S. Food and Drug Administration (US-FDA) as a dabrafenib mesylate salt (DBF center dot MS). Because of insolubility in aqueous medium, specifically at the pH 4-8 biorelevant range, DBF is a Biopharmaceutics Classification System (BCS) Class II drug (i.e., low solubility and high permeability). Therefore, screening of novel salts and cocrystals was carried out using Generally Recognized as Safe (GRAS) coformers. A total of 10 salts/cocrystals including the mesylate salt were found to be stable under the crystallization conditions. Among acidic coformers, methane sulfonic acid (MS) and saccharin (SACH) formed salts, while fumaric acid (FA), succinic acid (SA), and adipic acid (ADA) gave cocrystals. However, monoamines formed a monohydrate salt where the water molecule is hydrogen bonded with the aminopyrimidine moiety of DBF. The replacement of monoamines with ethylenediamine (EN) dislocated the water molecule near the free amine of EN in the crystal structure with a change in space group from triclinic (P (1) over bar) to monoclinic (P2(1)/n). Dissolution measurements at pH 1.2 (0.1 N HCl) showed that DBF center dot EN superset of H2O dissolved rapidly compared to the DBF.MS salt (the dissolution rate of DBF center dot EN superset of H2O and DBF center dot MS is 11 and 2 times faster than that of DBF). Structure-activity relationship analysis showed that bonding of the aminopyrimidine moiety with strong hydrogen bond synthons inhibited dissolution, whereas a loosely bound or free site at the aminopyrimidine moiety enhanced the dissolution rate. Finally, a cytotoxicity study was performed for DBF, DBF center dot MS, and DBF center dot EN superset of H2O, which showed that DBF center dot EN superset of H2O is safe for normal cells and yet equally potent against cancer cells. Crystal engineering of an improved formulation of dabrafenib center dot ethylenediamine hydrate is presented as a new anticancer drug.

Naftopidil molecular salts with improved dissolution and permeation - Mannava, M. K. Chaitanya; Dandela, Rambabu; Tothadi, Srinu; Solomon, K. Anand; Nangia, Ashwini K. (Crystal Growth & Design, 2020)
Naftopidil (NFPD) is a alpha 1 adrenoceptor antagonist drug. Low solubility and low permeability are the major drawbacks of this drug. The synthesis of multicomponent crystalline forms of this amine functional group drug with carboxylic acid coformers, both achiral and chiral acids, provides a solution to improve its solubility as well as permeability. Nine molecular salts were crystallized by liquid-assisted grinding followed by isothermal crystallization. Single-crystal X-ray diffraction analysis of the molecular salts showed that the structures are stabilized by strong N-H center dot center dot center dot O and O-H center dot center dot center dot O and weak C-H center dot center dot center dot O hydrogen bonds in the solid state. The bulk phase purity of new solid forms was confirmed by powder X-ray diffraction (PXRD), and the crystalline products were further characterized by IR spectroscopy and thermal analytical techniques (differential scanning calorimetry). The molecular salts exhibit superior dissolution rates compared to pure NFPD. However, during dissolution, NFPD showed decrease in concentration after 60 min for all salts due to precipitation. The supersaturation occurred due to salt disproportionation, which generates insoluble NFPD, as confirmed by PXRD of the residue. The salts reach high saturation concentration before 60 min, which is indicative of immediate release formulation to achieve fast onset of therapeutic activity. Moreover, the salts exhibit high saturation in phosphate buffer saline media and improved permeability compared to the pure drug. Finally, the D,L-malic acid racemate of NFPD shows enhanced dissolution and permeability compared to all other salts and pure NFPD.

Novel pharmaceutical cocrystals and salts of bumetanide - Allu, Suryanarayana; Bolla, Geetha; Tothadi, Srinu; Nangia, Ashwini K. (Crystal Growth & Design, 2020)
New crystalline forms of bumetanide, namely, four cocrystals, two salts, and one salt-cocrystal were crystallized. Urea and lactams such as valerolactam, caprolactam, and N-methyl caprolactam formed cocrystals with bumetanide, whereas 4-aminopyridine gave a salt. Piperazine afforded a salt hydrate, and 5-fluorocytosine gave a salt-cocrystal. The supramolecular synthons in bumetanide-lactam cocrystals are an amide dimer between drug and coformer, and acid homo dimer between bumetanide molecules. In bumetanide salts, the acid proton is transferred from bumetanide to coformer amine, whereas in bumetanide salt-cocrystal proton transfer and free acid were observed in the crystal structure. Similarly, the cytosine salt-cocrystal of bumetanide and fluorocytosine also gave a salt-cocrystal adduct. The acid proton of bumetanide is transferred to the 2-amino pyridine base of cytosine as a salt, and on the other side of the drug molecule the sulfonamide interacts with the syn amide part of cytosine. Furthermore, solubility, dissolution, and diffusion membrane permeability experiments were performed on all new solid forms. The piperazine salt shows high dissolution and permeability crossover when compared to other binary forms of bumetanide.

Salts and cocrystal of etodolac: advantage of solubility, dissolution, and permeability - Rai, Sunil K.; Allu, Suryanarayana; Nangia, Ashwini K. (Crystal Growth & Design, 2020)
{Etodolac (ETD) is a nonsteroidal anti-inflammatory drug (NSAID) approved by the United States Food and Drug Administration (US-FDA) in 1991 for the treatment of rheumatoid arthritis. Because of its poor aqueous solubility and high permeability, ETD falls under Biopharmaceutics Classification System (BCS) Class II drug. The present study was aimed to screen stable salts and cocrystals of ETD using Generally Recognized as Safe (GRAS) and a few non-GRAS coformers. Crystallization of five salts (i.e.

Can we identify the salt-cocrystal continuum state using XPS? - Tothadi, Srinu; Shaikh, Tabrez Rafique; Gupta, Sharad; Dandela, Rambabu; Vinod, Chathakudath P.; Nangia, Ashwini K. (Crystal Growth & Design, 2021)
X-ray photoelectron spectroscopy (XPS) is used to understand the nature of acid-base crystalline solids, to know whether the product is a salt (proton transfer, O-center dot center dot center dot H-N+) or a cocrystal (neutral adduct, O-H center dot center dot center dot N). The present study was carried out to explore if intermediate states of proton transfer from COOH to nitrogen (the proton resides between hydrogen bonded to O and N, O center dot center dot center dot H center dot center dot center dot N, quasi state) can be differentiated from a salt (complete proton transfer, N+-H center dot center dot center dot center dot O-) and cocrystal (no proton transfer, O-H center dot center dot center dot N) using N 1s XPS spectroscopy. The intermediate states of proton transfer arise when the pK(a) difference between the acid and the conjugate base is between -1 and 4, -1 < Delta pK(a) < 4, a situation common with COOH and pyridine functional groups present in drug molecules and pharmaceutically acceptable coformers. Complexes of pyridine N bases with aromatic COOH molecules in nine salts/cocrystals were cocrystallized, and their N 1s core binding energies in XPS spectra were measured. The proton state was analyzed by single-crystal X-ray diffraction for confirmation. Three new complexes were crystallized and analyzed by XPS spectra (without knowledge of their X-ray structures), to assess the predictive ability of XPS spectra in differentiating salt-cocrystal intermediate states against the extremities. The XPS results were subsequently confirmed by single-crystal X-ray data. Complexes of 3,5-dinitrobenzoic acid and isonicotinamide in 1:1 and 1:2 ratios exist as a salt and a salt-cocrystal continuum, respectively, as shown by the N 1s core binding energies. The proton states of the crystalline solids by XPS are in good agreement with the corresponding crystal structures. Other complexes, such as those of 3,5-dinitrobenzoic acid with 1,2-bis(4-pyridyl)ethylene, exhibit a salt-cocrystal continuum, maleic acids with 1,2-bis(4-pyridyl)ethylene and acridine are salts, 2-hydroxybenzoic acid and acridine is a salt, and the complex of 3,5-dinitrobenzoic acid and 3-hydroxypyridine is a salt and salt-cocrystal continuum, while fumaric acids with 1,2-bis(4-pyridyl)ethylene and acridine are cocrystals. Furthermore, three new acidbase complexes of 3,5-dinitrobenzoic acid with phenazine, 4-hydroxypyridine, and 4-cyanopyridine were studied initially by XPS and then confirmed by X-ray diffraction. In summary, since the N 1s binding energies cluster in a narrow range as cocrystals (398.7-398.9 eV) and salts (400.1-401.1 eV), it is clearly possible to differentiate between cocrystals and salts, but the saltcocrystal continuum values in XPS spectra are clustered in an intermediate range of cocrystals and salts but overlap with those of cocrystal or salt binding energies.

Enhanced solubility, permeability, and tabletability of nicorandil by salt and cocrystal formation - Mannava, M. K. Chaitanya; Gunnam, Anilkumar; Lodagekar, Anurag; Shastri, Nalini R.; Nangia, Ashwini K.; Solomon, K. Anand (Crystengcomm, 2021)
Cocrystallization is a rational selection crystal engineering approach for the development of novel solid forms with enhanced physicochemical and mechanical properties. Nicorandil (NCR) is a niacinamide vitamin derivative used to treat angina pectoris. A binary solid form screen of NCR with homologous dicarboxylic acids afforded NCR-oxalic acid (NCR-OA, 1:1), NCR-fumaric acid (NCR-FA, 1:1), NCR-succinic acid (NCR-SA, 1:1), and NCR-suberic acid (NCR-SBA, 1:0.5). The binary solids were characterized by powder X-ray diffraction, IR and NMR spectroscopy, and DSC. NCR-FA and NCR-SBA were crystallized by slow evaporation from chloroform and toluene solvents, respectively. Single crystal X-ray diffraction confirmed that NCR-FA is a molecular salt, while NCR-SBA is a neutral cocrystal. NCR and the FA anion are connected via the robust carbovlate-pyridinium synthon, whereas in the NCR-SBA cocrystal, the components associate via the carboxylic acid- -pyridine synthon. The phase stability, solubility, dissolution rate, diffusion rate and tabletability studies have demonstrated that the binary solids exhibit improved physical and mechanical properties compared to the NCR drug. Specifically, the NCR-FA salt and NCR-SBA cocrystal have higher solubility, dissolution rate, and hardness at lower pressures, making the formulation suitable for tablet compression.

Entacapone polymorphs: crystal structures, dissolution, permeability, and stability - Bommaka, Manish Kumar; Mannava, M. K. Chaitanya; Rai, Sunil K.; Suresh, Kuthuru; Nangia, Ashwini K. (Crystal Growth & Design, 2021)
Entacapone (ETP) is a catechol-O-methyltransferase (COMT) drug used to treat Parkinson's disease. ETP is available in the marketplace under the brand name Comtan since 2010, and ETP form-I was first reported in a patent published in 2001. However, analysis of its Xray crystal structures and stability relationship of ETP polymorphs and their dissolution and permeability profile have not yet been reported. We crystallized two new conformational polymorphs of ETP from a water and acetone mixture and studied the structural origin of polymorphism and their phase transformations, stability, equilibrium solubility, dissolution, and permeability properties. The ETP molecule adopts different conformations in the polymorphic structures with slight changes in carbonyl and nitrile group orientations. Thermal analysis suggests that form-III and form-IV are enantiotropically related to form-I, which is the thermodynamically stable form at ambient conditions. In contrast, form-II is monotropically related to form-I. Equilibrium solubility, dissolution, and permeability studies show that form-II persists in the slurry medium and dissolves faster with a high flux rate compared to the stable form-I in phosphate buffer solution at 37 +/- 0.5 degrees C.

Salts, solvates and hydrates of the multi-kinase inhibitor drug pazopanib with hydroxybenzoic acids - Rai, Sunil K.; Baidya, Debjani; Nangia, Ashwini K. (Crystengcomm, 2021)
The marketed formulation of pazopanib (PAZ) suffers from low and variable bioavailability because of its poor dissolution rate and photostability issues. The drug falls under Biopharmaceutics Classification System (BCS) class II of low solubility and good permeability. The hydrogen bonds and supramolecular interactions in crystalline forms of PAZ with hydroxybenzoic acids (HBAs) and dihydroxybenzoic acids (DHBAs), as well as its salts are analyzed. Ten X-ray crystal structures of PAZ which include the reference drug, a tetrahydrofuran solvate (PAZ center dot THF) and eight salts with HBAs/DHBAs are reported. There is proton transfer from the carboxylic group of the coformer acid to the most basic nitrogen atom of the 2-aminopyrimidine ring of PAZ in all cases. Two salts were crystallized in neat form, while the remaining six are solvates and hydrates. The crystal structure of PAZ is stabilized by sulfonamide and 2-aminopyrimidine homosynthons of N-HMIDLINE HORIZONTAL ELLIPSISO and N-HMIDLINE HORIZONTAL ELLIPSISN hydrogen bonds in an R2(2)(8) ring motif. PAZ center dot HBA/DHBA salts consistently contain the aminopyridiniumMIDLINE HORIZONTAL ELLIPSIScarboxylate N+-HMIDLINE HORIZONTAL ELLIPSISO- synthon of the R2(2)(8) ring. The sulfonamide homosynthon of PAZ is disrupted in preference to the formation of N-HMIDLINE HORIZONTAL ELLIPSISO and N-HMIDLINE HORIZONTAL ELLIPSISN hydrogen bonds in salt structures. The presence of an additional basic nitrogen atom in the indazole ring of PAZ promotes hydration and solvation through the O-HMIDLINE HORIZONTAL ELLIPSISN hydrogen bond. Whereas the formation of salts is desirable for pharmaceutical formulation, the inclusion of adventitious solvent and/or water molecules with hydroxybenzoic acid coformers in the cocrystal-salt products is a limitation for this class of coformers. The stability problem faced with hydrates and solvates of PAZ center dot HBA/DHBA salts means that their formation must be carried out by strictly anhydrous procedures. The consistent occurrence of the aminopyridiniumMIDLINE HORIZONTAL ELLIPSIScarboxylate N+-HMIDLINE HORIZONTAL ELLIPSISO- ring synthon is discussed in relation to the previous results of Aakeroy, Nangia and Zaworotko groups on similar acid-base multi-component systems.

The effects of cis and trans butenedioic acid on the physicochemical behavior of lumefantrine - Tomar, Devendrasingh; Lodagekar, Anurag; Gunnam, Anilkumar; Allu, Suryanarayana; Chavan, Rahul B.; Tharkar, Minakshi; Ajithkumar, T. G.; Nangia, Ashwini K.; Shastri, Nalini R. (Crystengcomm, 2022)
The present work investigates the effects of cis and trans butenedioic acid isomers (maleic acid and fumaric acid) on the crystallinity and pharmaceutical behavior of lumefantrine. Differential scanning calorimetry (DSC), powder X-ray diffraction (PXRD), attenuated total reflectance infrared spectroscopy (ATR-IR), solid-state nuclear magnetic resonance spectroscopy (ss-NMR), and single-crystal X-ray diffraction (SC-XRD) studies were employed. Lumefantrine-fumaric acid crystallized as a salt in the monoclinic space group P2(1)/c. In comparison, DSC and PXRD showed the formation of a co-amorphous solid with maleic acid. Complete proton transfer with a strong ionic interaction led to crystalline salt formation with the trans isomer, whereas weaker/fewer hydrogen bonds with the cis isomer of butenedioic acid led to a co-amorphous salt. The in vitro dissolution of both salts resulted in a similar 2.6-2.7-fold improvement in dissolution rate when compared to that of the crystalline lumefantrine. The crystalline and co-amorphous salts were stable under accelerated stability conditions (40 +/- 2 degrees C and 75 +/- 5% RH) for one month.

Fluorobenzoic acid coformers to improve the solubility and permeability of the BCS class IV drug naftopidil - Mannava, M. K. Chaitanya; Bommaka, Manish K.; Dandela, Rambabu; Solomon, K. Anand; Nangia, Ashwini K. (Chemical Communications, 2022)
Crystalline salts of the low solubility and low permeability drug naftopidil were investigated with mono-, di-, tri-, and tetrafluorobenzoic acids as coformers to show that 245TFBA (2,4,5-trifluorobenzoic acid) is the optimal salt with faster dissolution and high permeability, thereby opening the study of fluorinated coformers in pharmaceutical cocrystals and salts.

Novel crystal forms of Entresto: a supramolecular complex of trisodium sacubitril/valsartan hemi-pentahydrate - Shaikh, Tabrez R.; George, Christy P.; Bhukya, Priyanka; Shelke, Nikita; Pawar, Komal; Garai, Abhijit; Dandela, Rambabu; Gonnade, Rajesh G.; Nangia, Ashwini K. (Crystengcomm, 2022)
Entresto is a salt-cocrystal supramolecular complex with the chemical name trisodium sacubitril/valsartan hemi-pentahydrate for treating chronic heart failure and was approved by the US FDA in 2015. This multidrug complex was synthesized in our laboratory to investigate its polymorphic behavior. Different crystallization conditions, including various solvent systems, yielded different novel solid forms of Entresto (Form-I to Form-VI), including the reported form. All the novel solids are solvent-dependent and were reproducibly crystallized on a 10 g scale quantity. The 1H NMR spectra confirmed the 1 : 1 stoichiometry of the two drugs, namely, sacubitril and valsartan, in all the solid forms of the crystalline products. Powder X-ray diffraction and DSC analysis of the crystalline solids established that they are distinct crystalline forms. Stability studies under ambient conditions carried out over a one-year period showed higher stability for Form-I and Form-III compared to the other forms, including the innovator crystal form (labelled as Form-II). The novel crystal forms (notably Form-I and Form-III) exhibit higher stability and less hygroscopicity than the reported Form-II.

Synthesis of ternary cocrystals, salts, and hydrates of acefylline with enhanced dissolution and high permeability - Allu, Suryanarayana; Garai, Abhijit; Chernyshev, Vladimir V.; Nangia, Ashwini K. (Crystal Growth & Design, 2022)
Acefylline (ACF) is a stimulant xanthine derivative drug, which is formulated as a piperazine salt for the treatment of bronchial asthma. ACF falls under BCS class IV category of low solubility and poor permeability, which together limit the bioavailability and efficacy of the drug. In this work, ACF binary and ternary cocrystals, salts–cocrystals, and their polymorphs are synthesized by cocrystallization with several coformers. Two different methods were adopted for the supramolecular assembly of the ternary systems A.B.C: (1) first, binary adducts A.B or A.C were crystallized by grinding a slurry of the components in a suitable solvent and then C was added and grinding was continued; and (2) all three components were taken in a solvent slurry and ground together. The former method was found to be superior in affording the ternary salt/cocrystal. The role of laboratory seeding is implicated to explain the variation in crystallization results at different stages of the project. Crystal structures of the product’s binary and ternary systems were solved by single-crystal X-ray diffraction and powder X-ray diffraction data for structure solution. The crystal structures show the recurrence of carboxylate–pyridinium and imidazole–acid heterosynthons in the binary and ternary adducts. The intermolecular interactions between ACF and the coformer are analyzed by Hirshfeld surfaces, 2D fingerprint plots, and an energy framework. The permeability of ACF increases in binary and ternary systems with selected coformers. The fast dissolution and high permeability of ACF-PIP make this salt an improved crystalline formulation of acefylline.

Cocrystallization of multi-kinase inhibitor pazopanib with fenamic acids: improving dissolution and inhibiting cell migration - Rai, Sunil K.; Gunnam, Anilkumar; Roy, Debopriya; Rajput, Raveena; Kulkarni, Kiran; Nangia, Ashwini K. (CrystEngComm, 2023)
A multi-kinase inhibitor, pazopanib (PAZ) is cocrystallized with cyclooxygenase (COX) inhibitor fenamic acids to investigate the dissolution rate and inhibition of cell migration in VEGF-triggered HUVEC cells to test the efficacy of stoichiometric drug-drug combinations. Crystallization experiments at the sub-milligram level in an acetonitrile-methanol mixture yielded two drug-drug salt forms of PAZ with flufenamic acid (FFA) and niflumic acid (NFA) as PAZ+center dot FFA-center dot ACN (an acetonitrile solvate named as form I) and PAZ+center dot NFA-. Structures of the crystal forms were characterized by single crystal X-ray diffraction (SC-XRD) method. Crystal structures revealed that the presence of a 2-aminopyrimidine group in PAZ is a strong partner for the carboxyl group in all solid forms, forming an acidMIDLINE HORIZONTAL ELLIPSISpyrimidine heterosynthon with COX inhibitor fenamic acids. To perform dissolution experiments and cell line analysis, the scale-up of both salt forms were done in the acetonitrile-methanol mixture through crystallization, which showed a polymorphic transformation in the case of PAZ+center dot FFA-center dot ACN (an acetonitrile solvate named form II). The thermodynamic stability of PAZ+center dot FFA-center dot ACN (form II) and PAZ+center dot NFA- were analysed using slurry experiment under ambient conditions in pH 1.2 (0.1 N HCl) buffer medium and the residual solid phase was characterized by powder XRD, which showed that PAZ+center dot FFA-center dot ACN (form II) was a metastable solid form while PAZ+center dot NFA- was a stable solid form. The dissolution experiments at gastric pH 1.2 showed that the rate of dissolution of PAZ+center dot FFA-center dot ACN was 10 times higher than PAZ+center dot NFA-. The cell migration assay suggested that PAZ+center dot FFA-center dot ACN inhibited similar to 25% and PAZ+center dot NFA- inhibited similar to 20% migration of HUVEC cells compared to PAZ alone. These investigations suggested that the drug-drug salts PAZ+center dot FFA- and PAZ+center dot NFA- would be potential combo drug candidates for clinical trials. Multi-drug crystalline salts of pazopanib with fenamic acids exhibit enhanced dissolution and 20% higher inhibition in the migration of HUVEC cells compared to the reference drug.

Dabrafenib-panobinostat salt: improving the dissolution rate and inhibition of BRAF melanoma cells - Rai, Sunil K.; Marverti, Gaetano; Gunnam, Anilkumar; Allu, Suryanarayana; Nangia, Ashwini K. (ACS Omega, 2023)
Cocrystallization of the drug-drug salt-cocrystal of the histone deacetylase inhibitor (HDACi) panobinostat (PAN) and b-rapidly accelerated fibrosarcoma (BRAF) inhibitor dabrafenib (DBF) afforded single crystals of a two-drug salt stabilized by N+-H center dot center dot center dot O and N+-H center dot center dot center dot N- hydrogen bonds between the ionized panobinostat ammonium donor and dabrafenib sulfonamide anion acceptor in a 12-member ring motif. A faster dissolution rate for both drugs was achieved through the salt combination compared to the individual drugs in an aqueous acidic medium. The dissolution rate exhibited a peak concentration (Cmax) of approximately 310 mg cm-2 min-1 for PAN and 240 mg cm-2 min-1 for DBF at a Tmax of less than 20 min under gastric pH 1.2 (0.1 N HCl) compared to the pure drug dissolution values of 10 and 80 mg cm-2 min-1, respectively. The novel and fast-dissolving salt DBF-center dot PAN+ was analyzed in BRAFV600E melanoma cells Sk-Mel28. DBF-center dot PAN+ reduced the dose-response from micromolar to nanomolar concentrations and lowered IC50 (21.9 +/- 7.2 nM) by half compared to PAN alone (45.3 +/- 12.0 nM). The enhanced dissolution and lower survival rate of melanoma cells show the potential of novel DBF-center dot PAN+ salt in clinical evaluation.

Inhibitory effect of curcumin-artemisinin co-amorphous on Tau aggregation and Tau phosphorylation - Dubey, Tushar; Sonawane, Shweta Kishor; Mannava, M. K. Chaitanya; Nangia, Ashwini K.; Chandrashekar, Madhura; Chinnathambi, Subashchandrabose (Colloid and Surfaces B-Biointerfaces, 2023)
Tau is a natively unfolded microtubule-associated protein. Tau neurofibrillary tangles are one of the hallmarks of Alzheimer's disease. The post-translational modifications of Tau lead to its pathological state. Phosphorylation is the key post-translational modification associated with Tauopathy. Curcumin is a polyphenolic compound pre-sent in the rhizomes of Curcuma longa. Curcumin has been reported to have remarkable medicinal properties in several diseases, but its poor solubility limits its therapeutic potency. Artemisinin is a sesquiterpene lactone, which has been known sience ancient times for its applications as a treatment for various diseases such as malaria, cancer, autoimmune disease, etc. In the present study, the potency of crystalline curcumin, crystalline artemisinin, and Cur-Art co-amorphous dispersion were evaluated against Tau pathology. The in-vitro ThS/ANS fluorescence and electron microscopy results suggested that curcumin and Cur-Art efficiently inhibited Tau aggregation. Furthermore, exposure to curcumin and Cur-Art co-amorphous restored the impaired nuclear transport in formaldehyde-stressed cells. Curcumin was also found to modulate the phosphorylation of Tau, which indicated the neuroprotective potency. Thus, curcumin and Cur-Art co-amorphous exhibit therapeutic potential against Tau protein in Alzheimer's disease.
Keywords: artemisinin; curcumin; Phosphorylation; Tau Aggregation

Polymorph II of hydroxyurea 150 years after its first synthesis - Rai, Sunil K.; Tothadi, Srinu; Arhangelskis, Mihails; George, Christy P.; Gonnade, Rajesh G.; Nangia, Ashwini K. (Crystengcomm, 2023)
A new polymorph of hydroxyurea (HU) was crystallized 150 years after its first synthesis. Due to its medicinal use in neoplastic diseases and sickle cell anemia, a high throughput screen of HU binary cocrystals was attempted. Instead of a cocrystal, an isoenergetic form II crystallized concomitantly with urea in methanol.